Penilaian Kinerja Pelayanan pada Pengembangan Pelabuhan Penyeberangan Kartini - Ahyar, Izzudin; Soetjipto, Jojok Widodo; Alfiah, Rindang (Institut Transportasi dan Logistik Trisakti, 2025)
This study aims to determine the development of Kartini Ferry Port based on service performance assessment. Service performance assessment was analyzed using two methods, namely identification of existing port suitability based on surveys, and Customer Satisfaction Index analysis through distributing questionnaires to respondents. Furthermore, development at Kartini Port uses the gap results from previous Customer Satisfaction Index analysis. Research variables are sourced from Minister of Transportation Regulation Number 39 of 2015 with 21 indicators to be analyzed. The research results show suitability identification at the existing Kartini Port received a score of 44 (less suitable) and the results from Customer Satisfaction Index analysis also received a value of 62.23% (quite satisfied). This shows the service performance at the Kartini Ferry Port is still not fully maximized. Results from the gap calculation show that there are 10 service indicators with a value smaller than minus one (< -1). This indicates that indicators need to be developed and improved in the future. The existing development of Kartini Ferry Port needs to be done is adding facilities that are not yet available, readjusting some facilities that have not been maximized, and adding some information that is still incomplete.